2009
DOI: 10.1111/j.1365-2958.2009.06925.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphate kinase 2: a modulator of nucleoside diphosphate kinase activity in mycobacteria

Abstract: SummaryMycobacteria encode putative class II polyphosphate kinases (PPKs). We report that recombinant PPK2 of Mycobacterium tuberculosis catalyses the synthesis of GTP from GDP using polyphosphate rather than ATP as phosphate donor. Unlike that of PPK1, this is the favoured reaction of PPK2. The sites of autophosphorylation, H115 and H247, as well as G74 were critical for GTP-synthesizing activity. Compromised survival of a ppk2 knockout (PPK2-KO) of Mycobacterium smegmatis under heat or acid stress or hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 24 publications
3
70
0
Order By: Relevance
“…The first characterized P. aeruginosa PPK2 belongs to the class I subfamily. Twelve proteins of the class I subfamily have been characterized and are known to catalyze nucleoside diphosphate phosphorylation (nucleoside triphosphate synthesis) (11,13,(16)(17)(18). On the other hand, the first characterized PPK2 catalyzing nucleoside monophosphate phosphorylation, known as polyP-AMP phosphotransferase (PAP), of A. johnsonii (13), belongs to the class II subfamily.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first characterized P. aeruginosa PPK2 belongs to the class I subfamily. Twelve proteins of the class I subfamily have been characterized and are known to catalyze nucleoside diphosphate phosphorylation (nucleoside triphosphate synthesis) (11,13,(16)(17)(18). On the other hand, the first characterized PPK2 catalyzing nucleoside monophosphate phosphorylation, known as polyP-AMP phosphotransferase (PAP), of A. johnsonii (13), belongs to the class II subfamily.…”
Section: Resultsmentioning
confidence: 99%
“…While we did not investigate the functions of class III PPK2, many researchers have concluded that polyP-driven nucleotide phosphorylation is important for the survival of microbial cells under conditions of stress or stationary phase (11,17,29). For instance, ppk2 knockout in Mycobacterium species affects intracellular nucleotide pools and impairs cell survival in macrophages (17).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, it has been shown that downregulation of ppk-1 in M. tuberculosis using the IPTG (isopropyl-␤-D-thiogalactopyranoside) antisense-inducible system results in a bacteriostatic effect for nearly 15 days, followed by a rapid bactericidal effect, thereby suggesting that ppk-1 is essential for M. tuberculosis growth in vitro and a potential drug target to combat tuberculosis (49). Rv3232c (ppk-2) has also been shown to be widely conserved in a number of human pathogens, regulates nucleotide diphosphate kinase activity, and is important for intracellular survival in mycobacteria (26). Rv0496 (ppx) has also been shown to possess polyphosphatase activity, showing a distinct preference for short-chain polyP as the substrate (50).…”
mentioning
confidence: 99%
“…In bacteria, some of the enzymes involved in polyP metabolism are polyphosphate kinase 1 (PPK-1), which catalyzes the reversible transfer of the terminal (␥) phosphate of ATP to form polyP, and polyphosphatase (PPX), which processively hydrolyzes the terminal residues of polyP to liberate P i (21)(22)(23). Polyphosphate kinase 2 (PPK-2) is another enzyme involved in polyP metabolism that drives synthesis of GTP and ATP using polyP as a phosphate donor (24)(25)(26).…”
mentioning
confidence: 99%
“…The requirement for NTPs and dNTPs, during stress conditions, might be getting mediated through the marginal modulation of the levels of T2. Nevertheless, NDK is nonessential for most bacterial systems, including M. tuberculosis [20], as other enzymes such as adenylate kinase [52] and polyphosphate kinase [53,54], which are present in M. smegmatis also (TIGR Database), might be able to synthesise NTPs and dNTPs, as in E. coli [52,53]. Therefore, M. smegmatis may not be entirely dependent on NDK modulation for NTPs and dNTPs and this may probably be the reason for the lack of significant modulation of NDK.…”
Section: Discussionmentioning
confidence: 99%